Medbesedilnost in retoričnost baročne asketično-meditativne proze Poljanskega rokopisa - Žejn, Andrejka (Primerjalna književnost, 2017)
The Poljane Manuscript, an extensive late-eighteenth-century ascetic-meditative manuscript, was created based on a German adaptation of Vita Christi (Life of Christ), a Catholic passion-play classic of spiritual education literature that focuses on the meditative contemplation of Christ's suffering. The motivation for creating the manuscript was its functionality and its goal was to guide the reader toward choosing an ascetic Christian life; at the same time, the numerous rhetorical and intertextual devices give the text a literary character. Several layers can be identified and analyzed in the text: a layer introducing the biblical story, which is intertextually transferred and complemented with specifiers, a layer of implicit and explicit non-underestimating argumentative persuasion and teaching, and a layer of achieving direct co-experience with the anthropomorphized Christ that is built on intertextual and rhetorical devices. This last layer also fulfills the manuscript's basic purpose.
Keywords: barok; Baroque; Christianity; devotional literature; intertextuality; krščanstvo; manuscripts; medbesedilnost; meditative prose; meditativna proza; nabožna književnost; Poljanski rokopis; retorične figure; rhetorical figures; rokopisi; Slovenian literature; slovensko slovstvo; The Poljane Manuscript